Bio‐Inspired Mechanotactic Hybrids for Orchestrating Traction‐Mediated Epithelial Migration. Issue 16 (23rd February 2016) - Cai, Pingqiang; Layani, Michael; Leow, Wan Ru; Amini, Shahrouz; Liu, Zhiyuan; Qi, Dianpeng; Hu, Benhui; Wu, Yun‐Long; Miserez, Ali; Magdassi, Shlomo; Chen, Xiaodong
Abstract : A platform of mechanotactic hybrids is established by projecting lateral gradients of apparent interfacial stiffness onto the planar surface of a compliant hydrogel layer using an underlying rigid substrate with microstructures inherited from 3D printed molds. Using this platform, the mechanistic coupling of epithelial migration with the stiffness of the extracellular matrix (ECM) is found to be independent of the interfacial compositional and topographical cues.